Interview: "The Small Things Paint the Big Picture" with Harm Paulsen - Wulf Hein (EXARC Journal, 2015)
I meet Harm Paulsen (70), the best known and longest working experimental archaeologist in Germany, in his apartment in Schleswig. Although the rooms aren't small, it is only possible to move around by holding in your belly and not breathing, as everywhere, standing, hanging or lying around, is evidence of Harm's professional and private life – a clear line between the two is not visible. There are roughly 15 wooden spears with projectiles of all ages in the umbrella stand, next to it a magnificent Viking helmet, bows, harpoons, lances, quivers... Many glass cabinets filled with exceptionally well made stone tools and beautiful fossils are lined up in the hallway, while a number of rooms, including the living room, are full of textbooks on various disciplines. A true wonderland for everyone who loves history as much as Paulsen. As the weather was sunny and clear, despite it being the beginning of December, we decide spontaneously to go for a walk; this turned into several hours of discussion on the history of Schleswig-Holstein over the last 10.000 years and included a guided tour of a tumulus, a visit to Harm’s favourite spot on the lake and a natural beauty.